Text Readability in 11th and 12th Grade English Textbook of Indonesian Senior High School with FKGL Formula - Putri Rafa Salihah; Sahiruddin Sahiruddin; Putu Dian Danayanti Degeng (Unipdu Jombang, 2020)
AbstractThis study analysed text readability on English textbooks of grade 11th and 12th on Indonesian senior high school with FKGL Formula available online at www.readable.com . This study utilised the Flesch Kincaid Grade Level formula by Rudolph Flesch (1948), through quantitative methods. The purpose of this study was to determine the level of readability of the reading texts in those two textbooks. The data of reading texts were 5 reading texts of grade 11th taken by using simple random sampling (recount and expository texts, to represent from a lot of texts) while 5 reading texts of grade 12th (procedure and expository texts to represent from a lot of texts). The results of this study indicate that the textbook is too easy to read and to comprehend for grade 11th of senior high school, does not 1 text that corresponds to grade 11. Hence, an average of 6.8 is obtained in grade 11th and is estimated for grades 7th. And an average of 11.6 in grade 12th is suitable for grade 12th with estimates for grades 12th. This is consistent with the scale of the FKGL calculation readability formula with a scale of 0-12 (such as score 7.1 is suitable for grade 7th, and 7.5 is suitable for grade 8th). Thus, an analysis of the level of readability of English textbooks is needed as the best information and best contribution for reading educators.Key Words: Readability, Textbook, and Flesch Kincaid Grade Level Formula AbstrakPenelitian ini menganalisis keterbacaan teks pada buku teks bahasa Inggris kelas 11 dan 12 di SMA Indonesia dengan Formula FKGL diakses dari www.readable.com . Penelitian ini menggunakan rumus Flesch Kincaid Grade Level oleh Rudolph Flesch (1948), melalui metode kuantitatif. Tujuan dari penelitian ini adalah untuk menentukan tingkat keterbacaan teks bacaan di kedua buku teks tersebut. Data teks bacaan adalah 5 teks bacaan kelas 11 yang diambil dengan menggunakan metode simple random sampling (teks pengalaman dan teks ekspositori prosedur, teks naratif dan teks laporan, untuk mewakili dari banyak teks) dan 5 teks bacaan kelas 12 (prosedur dan teks ekspositori, untuk mewakili dari banyak teks). Hasil penelitian ini menunjukkan bahwa buku teks itu terlalu mudah dibaca dan dipahami untuk kelas 11 SMA, dan memperoleh tidak 1 teks yang sesuai dengan kelas 11. Dan buku kelas 12 sesuai dengan tingkat kelas 12, memperoleh 1 teks yang sesuai dengan kelas 12. Namun, dalam hasil akhir perhitungan teks rata-rata dinyatakan bahwa, setiap buku teks kelas 11 tidak cocok untuk pembaca target kelas 11. Karena rata-rata 6,8 diperoleh di kelas 11 dan diperkirakan untuk kelas 7. Dan rata-rata 11,6 di kelas 12 sesuai untuk kelas 12 dengan perkiraan untuk kelas 12 dan 13. Ini konsisten dengan skala formula keterbacaan perhitungan FKGL dengan skala 0-12 (seperti skor 7.1 cocok untuk kelas 7, dan 7,5 cocok untuk kelas 8). Dengan demikian, analisis tingkat keterbacaan buku teks bahasa Inggris diperlukan sebagai informasi serta kontribusi terbaik untuk pendidik khususnya skill reading.Kata Kunci: Keterbacaan, Buku Teks, dan Flesch Kincaid Grade